2003
DOI: 10.1002/biof.5520190310
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonoids and iodine metabolism

Abstract: Flavonoids have inhibiting effects on the proliferation of cancer cells, including thyroidal ones. In the treatment of thyroid cancer the uptake of iodide is essential. Flavonoids are known to interfere with iodide organification in vitro, and to cause goiter. The influence of flavonoids on iodine metabolism was studied in a human thyroid cancer cell line (FTC-133) transfected with the human sodium/iodide transporter (NIS). All flavonoids inhibited growth, and iodide uptake was decreased in most cells. NIS mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
0
9
0
1
Order By: Relevance
“…These include thyrotropin receptor (Santini et al 2003), iodine uptake by the sodium iodide transporter (Schröder van der Elst et al 2003), type 1 5′-deiodinase (Ferreira et al 2002), transthyretin (Kohrle et al 1988), thyroid hormone receptor (Moriyama et al 2002), and the thyroid hormone–dependent growth of pituitary cells (Ghisari and Bonefeld-Jorgensen 2005). Depression of serum T 4 and T 3 has been reported by several authors in PFOS-exposed rats (Lau et al 2003; Luebker et al 2005; Seacat et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These include thyrotropin receptor (Santini et al 2003), iodine uptake by the sodium iodide transporter (Schröder van der Elst et al 2003), type 1 5′-deiodinase (Ferreira et al 2002), transthyretin (Kohrle et al 1988), thyroid hormone receptor (Moriyama et al 2002), and the thyroid hormone–dependent growth of pituitary cells (Ghisari and Bonefeld-Jorgensen 2005). Depression of serum T 4 and T 3 has been reported by several authors in PFOS-exposed rats (Lau et al 2003; Luebker et al 2005; Seacat et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Iodine uptake is not only an important step in thyroid hormone synthesis, but also a crucial exploitable mechanism for the treatment of differentiated (papillary and follicular) thyroid carcinoma with radioactive iodine. In this regard, among flavonoids thus far tested, myricetin would be an interesting modality for the treatment of thyroid carcinoma due to its capacity to increase iodide uptake and retention [67].…”
Section: Effects Of Phenolic Compounds On Thyroidmentioning
confidence: 99%
“…NIS half-life is approximately 5 days in the presence and approximately 3 days in the absence of TSH [5]. Schröder-van der Elst et al [20] showed that the inhibitory effect on iodide influx exerted by some flavonoids (kaempferol, apigenin, luteolin) is a consequence of decreased NIS mRNA expression. The XN-triggered up-regulation of iodide influx reported in this experiment cannot be explained in the same way.…”
Section: Discussionmentioning
confidence: 98%
“…Schröder-van der Elst et al [20] reported that most flavonoids decrease, whereas myricetin increases iodide uptake by 35% after 4 days of incubation at 5 lM using the human follicular thyroid cancer cell line (FTC133), which was stably transfected with the human NIS. We observed significant increase of iodide uptake in the nontransformed rat FRTL-5 cell line which was maximal after 2 and 3 days of incubation using a much lower concentration of XN (1 nM).…”
Section: Discussionmentioning
confidence: 99%